Research of Nurses' Patıent Safety Culture Perceptıons and Affectıon Factors - Ayşegül Yılmaz; Sergul Duygulu (Association of Nurse Managers, 2020)
INTRODUCTION: The culture of patient safety is an important element for the quality of health care delivery and is a global concern. In the development of patient safety culture, it is important to determine the factors affecting the patient safety culture.This study was performed in descriptive and cross-sectional design in order to determine nurses' perception of patient safety culture and the factors affecting it. METHODS: This study was conducted in four public hospitals across Turkey, in 2014. The study consisted of 427 staff nurses. Data were collected through the Demographic Data Form and Patient Safety Culture Hospital Questionnaire. RESULTS: The mean age of the nurses was 33.12 and 75.6% of them were training about patient safety culture. The overall level of patient safety culture was 49.3%. Nurses' working position, working year in the occupation, training on patient safety, nurses' thinking that the hospital they work in is a safe environment for patients and employees, working style, weekly working time and presence of practices related to hospital patient safety all had affected nurses' perceptions of patient safety culture, but this effect was found to be low. DISCUSSION AND CONCLUSION: According to the results of this study, a non-punitive approach to error reporting of nurses in hospitals should be put forward. In addition, it is important to regulate working systems and work environments in a way to ensure patient safety and to support the professional development of nurses for patient safety. It may also be suggested to identify other factors that affect patient safety culture in the health institutions where the study is conducted.